Improved mouse models and advanced genetic and genomic technologies for the study of neutrophils. Issue 6 (June 2020) - Hosur, Vishnu; Skelly, Daniel A.; Francis, Christopher; Low, Benjamin E.; Kohar, Vivek; Burzenski, Lisa M.; Amiji, Mansoor M.; Shultz, Leonard D.; Wiles, Michael V.
Highlights: The heterogeneity and diversity of neutrophils is important in a variety of diseases. Humanized PDX mice is an important resource to gaining clinically relevant knowledge of neutrophils. Three mouse diversity resources facilitate broad utility: the CC, DO, and BXD. Site-specific recombinases can aid in generating next-generation mouse models. Embracing novel mouse resources and harnessing new technologies, enables rapid development of novel therapeutics. Abstract : Mice have been excellent surrogates for studying neutrophil biology and, furthermore, murine models of human disease have provided fundamental insights into the roles of human neutrophils in innate immunity. The emergence of novel humanized mice and high-diversity mouse populations offers the research community innovative and powerful platforms for better understanding, respectively, the mechanisms by which human neutrophils drive pathogenicity, and how genetic differences underpin the variation in neutrophil biology observed among humans. Here, we review key examples of these new resources. Additionally, we provide an overview of advanced genetic engineering tools available to further improve such murine model systems, of sophisticated neutrophil-profiling technologies, and of multifunctional nanoparticle (NP)-based neutrophil-targeting strategies. Teaser: Advanced genetic engineering tools, humanized PDX mice, recombinant inbred strains, and highly diverse outbred mice provide valuable opportunities for exploring new avenues in translational research on neutrophils.